2008
DOI: 10.1002/ejoc.200800495
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Cross‐Coupling of Thiols with 1‐Iodo‐2‐chalcogenoalkenes

Abstract: We describe herein a new method for the synthesis of densely substituted alkenes containing chalcogenide atoms by a cross-coupling reaction between 1-iodo-2-chalcogenoalkenes and thiols using copper(I) as catalyst in a ligandfree system. The desired cross-coupling products were obtained in good yields and with satisfactory selectivity. The developed protocol tolerates a wide range of functional groups; the reactions of alkyl-, benzyl-, and arylthiols with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…One topic of special interest is the development of cross-coupling methodologies to carry out the reaction between ArX and RSH in water in the absence of organic ligands. CuI, without additional ligands, was used as a catalyst in the reaction of thiols with iodochalcogeno alkenes to give products in moderate to good yields . Recently, it was reported that thiophenol reacts with phenyl halides in water in the presence of Bu 4 NBr (TBAB) at 80 °C (Scheme ) .…”
Section: Catalytic Cross-coupling Reactions (Z = S Se Te)mentioning
confidence: 99%
See 1 more Smart Citation
“…One topic of special interest is the development of cross-coupling methodologies to carry out the reaction between ArX and RSH in water in the absence of organic ligands. CuI, without additional ligands, was used as a catalyst in the reaction of thiols with iodochalcogeno alkenes to give products in moderate to good yields . Recently, it was reported that thiophenol reacts with phenyl halides in water in the presence of Bu 4 NBr (TBAB) at 80 °C (Scheme ) .…”
Section: Catalytic Cross-coupling Reactions (Z = S Se Te)mentioning
confidence: 99%
“…CuI, without additional ligands, was used as a catalyst in the reaction of thiols with iodochalcogeno alkenes to give products in moderate to good yields. 187 Recently, it was reported that thiophenol reacts with phenyl halides in water in the presence of Bu 4 NBr (TBAB) at 80 °C (Scheme 60). 188 Product yields for the reaction involving ArSH and PhCH 2 SH were as high as 91-99%, whereas with BuSH the yield dropped to 15%.…”
Section: Cu-catalyzed Transformationsmentioning
confidence: 99%
“…In this way, the potential of 3-iodo-2-chalcogen-benzo[ b ]furan derivatives as precursors for increasing molecular complexity via palladium- and copper-catalyzed reactions has been briefly investigated (Schemes , , and ). For example, compound 5a underwent Ullmann-type coupling with different thiols and gave the corresponding 3-(arylthio)-2-(phenylselanyl)benzo[ b ]furans 6a and 6b in 75% and 74% yields, respectively (Scheme ). To further prove the utility of our cyclization products, we tested the reactivity of 5f toward CuI/bipyridine-catalyzed cross-coupling with diphenyl diselenides to afford the 2,3-bis(phenylselanyl)benzo[ b ]furan products in moderate yields (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…High yields and high E/Zselectivity were found, but catalyst recycling led to significant loss of activity. CuI without additional ligands was used as a catalyst in the reaction of thiols with iodochalcogeno alkenes to give product in moderate to good yields [72].…”
Section: Catalytic Cross-coupling Reactions J83mentioning
confidence: 99%